P66 Single-site versus multiport robotic hysterectomy in obese patients with endometrial cancer: a multicentre retrospective evaluation of surgical and oncological outcomes. (1st November 2019) - Vizza, E; Mereu, L; Bogliolo, S; Cela, V; Gardella, B; Certelli, C; Pellegrini, A; Posar, G; Tateo, S; Gadducci, A; Spinillo, A; Corrado, G
Abstract : Introduction/Background: The majority of women who undergo radical hysterectomy for endometrial cancer (EC) are obese and they may benefit from robotic surgery. The aim of this study is to compare robotic single-site hysterectomies (RSSH) and robotic multiport hysterectomies (RMPH) for EC in obese patients. Methodology: This study compares RSSH with RMPH in obese patients with EC and FIGO stage I or II. Data were collected from July 2010 to October 2018 in four Italian institutes: Regina Elena National Cancer Institute of Rome, Fondazione Policlinico San Matteo and University of Pavia, Santa Chiara Hospital of Trento and University of Pisa. According to their BMI, patients were divided in 3 classes: A from 30 to 34.9 kg/m 2, B from 35 to 39.9 kg/m 2 and C 40 kg/m 2 or higher. Results: We included 225 patients: 76 in the RSSH group divided, respectively, in 53, 18 and 5 in the A, B and C classes; 149 in the RMPH group divided, respectively, in 76, 37 and 36 in the A, B and C classes. In the RSSH group, the median operation time (OT) and blood loss (BL) were, respectively, 139 min and 50 ml in the A class, 142.5 min and 50 ml in the B class and 165 min and 100 ml in the class C. In the RMPH group, the median OT and the median BL were, respectively, 195 min and 100 ml in the class A, 170 min and 50 ml in the class B and 122.5 min and 75 ml in the class C. The conversion rate increased in the 3 classes, especially in the RSSH group (in the A, B and C classes, respectively, 1.8%, 5.5% and 60%). Conclusion: Technical difficulties in single-site surgery increase with the patients' BMI and when the BMI is 40 kg/m 2 or higher this technique is most of the times unfeasible. Disclosure: Nothing to disclose.